The enigma of the acquired immunodeficiency syndrome - Yaacob, Hashim; Park, A. Wallace (1987)
Investigative probes into the immunopathogenesis of the acquired immunodeficiency syndrome (AIDS) have now isolated a retrovirus known as HTL V Ill/LAV or Human Immunodeficiency Virus (HIV). However, in spite of this advance, the spectrum of clinical manifestations and case numbers continues to rise in conjunction with global spread. Although dental surgeons face a number of infectious diseases in their discipline including Hepatitis B, the emergence of the AIDS virus with attendant dramatic coverage by the media tends to emphasize the more fatal aspects and reinforces the point that there is neither a current drug with potential nor a vaccine on the horizon. Against this background, the article endeavours to put the disease into perspective with some diagnostic pointers and precautions during dental treatment. Infiltration of AIDS into Southeast Asia is inevitable but some insight of the implications and precautions should ensure the unimpeded treatment of patients.